RUSSIA-CHINA COOPERATION IN THE MIDDLE EAST: STRATEGIC ALLIANCES AND ECONOMIC INFLUENCE IN A MULTIPOLAR WORLD - Singh, Harpreet; Singh, Sirjan Paul (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Russia and China deepen Middle Eastern cooperation as the powers work to shift global balance of power. Both wield similar tools of diplomacy, economics, and security to underwrite their position throughout the region. It is an alliance not based on formal treaties but rather coordinated policies and shared presidential interests in counteracting the West. Russia has long-standing military and energy relationships with countries including Iran and Syria, using arms sales and joint projects for infrastructure to cement access and expand diplomatic ties. With its Belt and Road Initiative, port development, and energy contracts, China focuses on investment and trade and provides capital. Such actions breed trust and develop financial dependencies that expand China’s leverage. Such coordination constricts the space for Western-led sanctions and facilitates alternative trajectories for regional players. In many cases, Middle Eastern governments leverage engagement with the Russians and the Chinese to negotiate better terms with Western partners. Though the two powers come to the region with different sets of tools, their strategies often overlap. "Less involved in armed conflict, China supports post-conflict reconstruction." Russia, by contrast, uses limited military power — and then negotiates political settlements. These roles have a symbiotic relationship, enabling them both to thrive without competing against one another. This cooperation is restructuring economic flows, and decision-making, across oil markets, telecommunications, and defence procurement. This allows more acceptance of non-Western governance models. Hence the Middle East is an important arena of multipolarity in practice. The results are far from certain, but the expanding footprint of Russia and China in the region has long-term implications for global diplomacy and trade routes — with a lingering counterbalance wherever Western influence wanes or is contested. A sample of 239 was collected to find the result of the study. The factors that impact Strategic Alliances and Economic Influence of Russia & China cooperation in a Multipolar World are Geopolitical Shifts and Strategic Objectives, Economic Cooperation and Trade, Military and Security Cooperation, and Diplomatic Influence.